2006
DOI: 10.1530/rep.1.01069
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of acrosome reaction of fowl spermatozoa: evidence for the involvement of protein kinase C and protein phosphatase-type 1 and/or -type 2A

Abstract: The signal transduction pathways involved in the regulation of the acrosome reaction and motility of fowl spermatozoa were investigated. The motility and acrosomal integrity of fowl spermatozoa in TES/NaCl buffer, with or without homogenised inner perivitelline layers (IPVL), prepared from laid fowl eggs, was almost negligible at 40 8C. In the presence of 2 mmol CaCl 2 /l at 40 8C, motility became vigorous and the acrosome reaction was stimulated when IPVL was added. In the absence of Ca 2C , motility was stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
3
24
0
1
Order By: Relevance
“…Both the S/T phosphatases PP1 and PP2 are present in sperm and are found to participate in sperm capacitation, acrosome reaction, and motility (Furuya et al 1993, Ashizawa et al 2006, Chakrabarti et al 2007. In mammals, four PP1c isoforms were identified: PP1a, PP1b, PP1g1, and PP1g2, in which PP1g2 is testis/sperm specific and important for sperm motility and morphological processes during spermatogenesis (Chakrabarti et al 2007).…”
Section: Cmentioning
confidence: 99%
“…Both the S/T phosphatases PP1 and PP2 are present in sperm and are found to participate in sperm capacitation, acrosome reaction, and motility (Furuya et al 1993, Ashizawa et al 2006, Chakrabarti et al 2007. In mammals, four PP1c isoforms were identified: PP1a, PP1b, PP1g1, and PP1g2, in which PP1g2 is testis/sperm specific and important for sperm motility and morphological processes during spermatogenesis (Chakrabarti et al 2007).…”
Section: Cmentioning
confidence: 99%
“…Semen obtained from two to three males was suspended in Hanks' balanced salt solution (HBSS) containing 1.25 mmol/l of CaCl 2 and 0.1% (v/v) of proctodeal gland secretion. We decided to include CaCl 2 in the sperm extender because it is reported that the induction of AR by homogenized PL was almost negligible in the absence of Ca 2C (Ashizawa et al 2006). We added proctodeal gland secretion into the incubation mixture since it inhibits an agglutination of quail spermatozoa.…”
Section: Semen Collection and Preparationmentioning
confidence: 99%
“…mechanism is supported by Guan et al (2007) work that shows a direct activation of the S/T phosphatase PP2A by PRKCA which result in PI3K inhibition by dephosphorylation of PI3K. The S/T protein phosphatases PPP1 and PPP2 are found in sperm cells and participate in the capacitation and acrosome reaction processes (Furuya et al 1993, Ashizawa et al 2006, Chakrabarti et al 2007. Following this information, we hypothesized that the PRKCA-mediated PI3K inhibition during sperm capacitation occurs through PRKCA-dependent activation of PPP1 and/or PPP2.…”
Section: Regulation Of Pi3k In Spermmentioning
confidence: 84%
“…The S/T phosphatases PPP1 and PPP2 are present in sperm cells, and were found to participate in the capacitation and acrosome reaction processes, and sperm motility (Furuya et al 1993, Ashizawa et al 2006, Chakrabarti et al 2007). In the mammalian phylum, four PPP1C isoforms were identified: PPP1CA (PP1ca), PPP1CB (PP1cb), PPP1CC1 (PP1cg1), and PPP1CC2 (PP1cg2), of which the latter two are alternative splice variants of the PPP1CC gene.…”
Section: Introductionmentioning
confidence: 99%